The association between flow and oxygenation and cortical development in fetuses with congenital heart defects using a brain‐age prediction algorithm. (7th September 2020) - Everwijn, Sheila M. P.; Namburete, Ana I. L.; van Geloven, Nan; Jansen, Fenna A. R.; Papageorghiou, Aris T.; Teunissen, Aalbertine K.; Rozendaal, Lieke; Blom, Nico; van Lith, Jan M.; Haak, Monique C.
Abstract: Objectives: Presumably, changes in fetal circulation contribute to the delay in maturation of the cortex in fetuses with congenital heart defect (CHD). The aim of the current study is to analyze fetal brain development based on hemodynamic differences, using novel brain‐age prediction software. Methods: We have performed detailed neurosonography, including acquiring 3D volumes, prospectively in cases with isolated CHD from 20 weeks onwards. An algorithm that assesses the degree of fetal brain‐age automatically was used to compare CHD cases to controls. We stratified CHD cases according to flow and oxygenation profiles by lesion physiology and performed subgroup analyses. Results: A total of 616 ultrasound volumes of 162 CHD cases and 75 controls were analyzed. Significant differences in maturation of the cortex were observed in cases with normal blood flow toward the brain (−3.8 days, 95%CI [−5.5; −2.0], P = < . 001 ) and low (−4.0 days, 95% CI [−6.7; −1.2] P = < . 05 ; hypoplastic left heart syndrome[HLHS]) and mixed (−4.4 days, 95%CI [−6.4; −2.5] p = < . 001 ) oxygen saturation in the ascending aorta (TGA) and in cardiac mixing (eg, Fallot) cases. Conclusion: The current study shows significant delay in brain‐age in TGA and Fallot cases as compared to control cases. However, the small differences found in this study questions the clinical relevance.